Caveolae Link CaV3.2 Channels to BKCa-Mediated Feedback in Vascular Smooth Muscle. Issue 10 (October 2018) - Hashad, Ahmed M.; Harraz, Osama F.; Brett, Suzanne E.; Romero, Monica; Kassmann, Mario; Puglisi, Jose L.; Wilson, Sean M.; Gollasch, Maik; Welsh, Donald G.
Abstract : Objective—: This study examined whether caveolae position CaV 3.2 (T-type Ca2+ channel encoded by the α-3.2 subunit) sufficiently close to RyR (ryanodine receptors) for extracellular Ca 2+ influx to trigger Ca 2+ sparks and large-conductance Ca 2+ -activated K + channel feedback. Approach and Results—: Using smooth muscle cells from mouse mesenteric arteries, the proximity ligation assay confirmed that CaV 3.2 reside within 40 nm of caveolin 1, a key caveolae protein. Methyl-β-cyclodextrin, a cholesterol depleting agent that disrupts caveolae, suppressed CaV 3.2 activity along with large-conductance Ca 2+ -activated K + –mediated spontaneous transient outward currents in cells from C57BL/6 but not CaV 3.2 −/− mice. Genetic deletion of caveolin 1, a perturbation that prevents caveolae formation, also impaired spontaneous transient outward current production but did so without impairing Ca 2+ channel activity, including CaV 3.2. These observations indicate a mistargeting of CaV 3.2 in caveolin 1 −/− mice, a view supported by a loss of Ni 2+ -sensitive Ca 2+ spark generation and colocalization signal (CaV 3.2-RyR) from the proximity ligation assay. Vasomotor and membrane potential measurements confirmed that cellular disruption of the CaV 3.2-RyR axis functionally impaired the ability of large-conductance Ca 2+ -activated K + to set tone in pressurized caveolin 1 −/− arteries. Conclusions—: Caveolae play a critical role in protein targeting and preserving the close structural relationship between CaV 3.2 and RyR needed to drive negative feedback control in resistance arteries. Abstract : Supplemental Digital Content is available in the text.